1999
DOI: 10.1177/204748739900600106
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Angiogenesis: Protein and Gene Therapy Delivery Strategies

Abstract: Angioplasty and surgical bypass, the primary interventional therapies for the treatment of atherosclerosis, are limited by the development over time of native vessel restenoses and graft occlusions. Furthermore, these therapies are not options for a significant number of individuals in whom the extent of vascular pathology is especially severe or widespread. Angiogenesis, the growth of new vasculature, is a critical biological response to ischemia that provides collateralization, or 'biological revascularizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 149 publications
0
24
0
Order By: Relevance
“…Preliminary results utilizing this approach as the sole therapy for patients with chronic myocardial ischemia suggest that direct injection of VEGF as naked DNA into cardiac myocytes may improve collateral blood flow and reduce the frequency of, and threshold for, myocardial ischemia (Losordo et al, 1998;Symes et al, 1999). Therapeutic angiogenesis is an innovative approach to the treatment of ischemic diseases, whereby the administration of the VEGF gene facilitates the "biological revascularization" of obstructed vascular segments, and the reperfusion of ischemic tissues (Rosengart et al, 1999). Moreover, it has been suggested that in certain cases of heart failure, the angiographically occult intramural coronary vasculature consists the locus of the disease as well as the cure .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preliminary results utilizing this approach as the sole therapy for patients with chronic myocardial ischemia suggest that direct injection of VEGF as naked DNA into cardiac myocytes may improve collateral blood flow and reduce the frequency of, and threshold for, myocardial ischemia (Losordo et al, 1998;Symes et al, 1999). Therapeutic angiogenesis is an innovative approach to the treatment of ischemic diseases, whereby the administration of the VEGF gene facilitates the "biological revascularization" of obstructed vascular segments, and the reperfusion of ischemic tissues (Rosengart et al, 1999). Moreover, it has been suggested that in certain cases of heart failure, the angiographically occult intramural coronary vasculature consists the locus of the disease as well as the cure .…”
Section: Discussionmentioning
confidence: 99%
“…Angiogenic gene therapy to promote the development of supplemental collateral blood vessels in chronic myocardial ischemia has been exploited using direct myocardial administration of the vascular endothelial growth factor (VEGF) gene, in the form of naked DNA (Rosengart et al, 1999). Preliminary results using this strategy suggest that it may constitute an alternative treatment for patients with severe myocardial ischemia (Losordo et al, 1998;Symes et al, 1999) and heart failure (Carmeliet et al, 1999;Isner et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, these therapies are not options for a significant number of individuals in whom the extent of vascular pathology is especially severe or widespread. Angiogenesis, the growth of new vasculature, is a critical biological response to ischemia that provides collateralization, or ''biological revascularization'' of vascular obstructions [45]. Evidence exists to support the concept that a graft lined with a significant number of endothelial cells (EC) would consequently lead better graft survival [46] LELI has been demonstrated to positively influence cellular proliferation for the process of angiogenesis on EC [2,47].…”
Section: Discussionmentioning
confidence: 99%
“…1,2 This approach is based on the knowledge that in the adult heart, the genes coding for angiogens and their receptors are expressed in low levels, apparently insufficient in most individuals to provide robust formation of collaterals in response to chronic ischemia. 3,4 Vascular endothelial growth factor (VEGF), a protein coded by a 7-exon gene localized on chromosome 6, serves as a major angiogen in normal cardiac development.…”
mentioning
confidence: 99%